Fanconi anemia with sun-sensitivity caused by a Xeroderma pigmentosum-associated missense mutation in XPF - Isabell Popp; Maqsood Punekar; Nick Telford; Stavros Stivaros; Kate Chandler; Meenakshi Minnis; Anna Castleton; Claire Higham; Louise Hopewell; D. Gareth Evans; Anja Raams; Arjan F. Theil; et al. (BMC, 2018)
Abstract Background Fanconi anemia (FA) is an inherited genomic instability disorder with congenital and developmental abnormalities, bone marrow failure and predisposition to cancer early in life, and cellular sensitivity to DNA interstrand crosslinks. Case presentation A fifty-one-year old female patient, initially diagnosed with FA in childhood on the basis of classic features and increased chromosomal breakage, and remarkable sun-sensitivity is described. She only ever had mild haematological abnormalities and no history of malignancy. To identify and characterise the genetic defect in this lady, who is one of the oldest reported FA patients, we used whole-exome sequencing for identification of causative mutations, and functionally characterized the cellular phenotype. Detection of the novel splice site mutation c.793-2A > G and the previously described missense mutation c.1765C > T (p.Arg589Trp) in XPF/ERCC4/FANCQ assign her as the third individual of complementation group FA-Q. Ectopic expression of wildtype, but not mutant, XPF/ERCC4/FANCQ, in patient-derived fibroblasts rescued cellular resistance to DNA interstrand-crosslinking agents. Patient derived FA-Q cells showed impaired nuclear excision repair capacity. However, mutated XPF/ERCC4/FANCQ protein in our patient's cells, as in the two other patients with FA-Q, was detectable on chromatin, in contrast to XP-F cells, where missense-mutant protein failed to properly translocate to the nucleus. Conclusions Patients with FA characteristics and UV sensitivity should be tested for mutations in XPF/ERCC4/FANCQ. The missense mutation p.Arg589Trp was previously detected in patients diagnosed with Xeroderma pigmentosum or Cockayne syndrome. Hence, phenotypic manifestations associated with this XPF/ERCC4/ FANCQ mutation are highly variable.